Heterogeneous Recommendations for School Attendance in Children With Chronic Kidney Diseases During the COVID-19 Pandemic in Europe - Schild, Raphael; Hopf, Luke; Loos, Sebastian; Oh, Jun; Levtchenko, Elena (Frontiers in Pediatrics, 2021)
Introduction: After worldwide closures due to the COVID-19 pandemic, schools have reopened in most European countries in late 2020. Consequently, for children with chronic diseases the risks of COVID-19 have to be weighed against the long-time risks of missing school. Methods: To evaluate the impact of chronic diseases on school attendance for children in Europe during the COVID-19 pandemic we conducted a survey among members of the European Society for Pediatric Nephrology (ESPN) between September and November 2020. We asked for current forms of schooling, the existence of national guidelines, parental concerns, and the pediatric nephrologists recommendations for school attendance for specific virtual patients with chronic kidney disease (CKD). Results: Recommendations varied widely among pediatric nephrologists. A minority stated that specific recommendations for COVID-19 risk in children with kidney diseases existed in their country from local health authorities (9 of 29 countries; 31%) and/or national pediatric nephrology societies (9 of 29 countries; 31%). Over 90% of physicians have experienced parents keeping their children out of school against medical advice of their health providers and about 50% have experienced their patients being refused by school authorities. Consequently, 25% of all pediatric nephrologists estimated that more than 10% of their patients will not attend school regularly. Conclusion: COVID-19 causes educational deficits in the already vulnerable population of children with CKD. As the evidence for the course of COVID-19 in children with chronic diseases grows, rapidly adapted recommendations from pediatric societies could help reduce uncertainty among doctors, patients, and parents.